A retrospective observational study of clinicopathological spectrum of ovarian tumors - Purnima Upreti; Gaddam Thapasya Reddy (Barpeta Obstetrics and Gynaecological Society, 2021)
Objectives: We aim to study the clinical features and histopathological pattern of ovarian tumors in different age groups which shall add on to the current data on demography and clinical spectrum of ovarian tumors. Methods: The retrospective study was done over a period of 5 years (2012-2017); where we included women who underwent surgery for ovariotomy alone or along with hysterectomy. Histopathological examination of the specimens and reporting was done based on WHO classification of ovarian tumors. The data was entered in MS EXCEL spreadsheet and analysed. Results: Out of 172 ovarian tumors, 82.6% were benign, 12.8% were malignant. Common clinical presentation in majority of patients (48.84%) was pain in abdomen. Epithelial tumors formed the main bulk of neoplasms (61.6%). The majority of epithelial tumors were serous tumors (54.7%) followed by mucinous (41.5%). Benign tumors were more (53.52%) in the reproductive age group (21-40 years) and malignant tumors were more common in postmenopausal age group. Mature cystic teratoma was the most common type of benign tumor followed by serous cystadenoma. Serous cystadenocarcinoma was the most common type of malignant neoplasm followed by granulosa cell tumour. Conclusion: There is a different clinical presentation and age distribution of various histopathological types of ovarian cancers; with benign exhibiting reproductive age group and malignant exhibiting perimenopausal age group. Yet, to confirm, all the ovarian masses must be examined histopathologically for definite diagnosis and management.